KAJIAN INTERTEKSTUAL NOVEL CINTA BERTABUR DI LANGIT MEKKAH KARYA ROIDAH DAN NOVEL ASMARA DI ATAS HARAM KARYA ZULKIFLI L. MUCHDI DENGAN PENDEKATAN SOSIOLOGI - Nurul Azizah, Ririn (Ruang Kata, 2021)
Literary works in this era of progress have been very developed. The creation of literary works is usually influenced by the literary works that preceded it. The literary work that precedes is used as an example or role model for later literary works. Two or more literary works with the same theme have similarities and differences. Similarities and differences in several literary works can be analyzed using the principle of intertextuality. This principle is intended to examine texts that are considered to have a certain relationship with other texts so that it is possible for a work to become a hypogram for subsequent literary works. In this study the author chose the title " Intertextual Study of the Novel Cinta Bertabur Di Langit Mekkah by Roidah and Novel Asmara Di Atas Haram by Zulkifli L. Muchdi with a Sociological Approach ". Based on the object studied, this study aims to describe: (1) the structure of Roidah's novel Cinta Bertabur Di Langit Mekkah (CBM) and novel Asmara Di Atas Haram (ADH) by Zulkifli L. Muchdi, (2) similarities and differences in the novel Cinta Bertabur Di Langit Mekkah (CBM) by Roidah and novel Asmara Di Atas Haram (ADH) by Zulkifli L. Muchdi, (3) Intertextual relations between Roidah's novel Cinta Bertabur Di Langit Mekkah (CBM) and Zulkifli L. Muchdi's novel Asmara Di Atas Haram (ADH, and (4) sociological aspects of novel Cinta Bertabur Di Langit Mekkah (CBM) by Roidah and novel Asmara Di Atas Haram (ADH) by Zulkifli L. Muchdi. The method used is descriptive analysis method. The results obtained in the research are intrinsic elements of the novel, similarities and differences between the two novels, intertextual relations and sociological aspects which include social aspects, religious aspects, economic aspects, and love aspects.